Inventories, Employment and Hours - Marzio Galeotti; Louis J. Maccini; Fabio Schiantarelli (Institute for the Study of Labor (IZA), 2002)
The purpose of this paper is to develop a model that integrates inventory and labor decisions. We extend a model of inventory behavior to include a detailed specification of the role of labor input in the production process and of the costs associated with it. In particular, we distinguish between employment, hours and effort per worker, and allow for adjustment costs associated with employment changes. We assume that the requirement function for effective hours has a general trans-logarithmic form, and derive an estimable system of Euler equations for inventories and employment with implied cross-equation restrictions. The econometric results shed light on several important topics, including the shape of the marginal cost of output and the role of labor hoarding as an explanation of procyclical productivity and the persistence of inventory stocks. Moreover, they raise questions about the adequacy of commonly used specifications such as Cobb-Douglas approximations to the production process and the definition of labor input as the product of employment and effective hours worked per worker.
Keywords: J24; J23; D24; E24; E23; J32; 330; Inventories; employment; hours; labor adjustment costs; procyclical productivity; Betriebliche Lagerhaltung; Arbeitsnachfrage; Anpassungskosten; Lagerzyklus; Theorie